Single Amino Acids G196 and R198 in hr1 of Subgroup K Avian Leukosis Virus Glycoprotein Are Critical for Tva Receptor Binding - Chen, Jian; Li, Jinqun; Li, Lizhen; Liu, Peng; Xiang, Yong; Cao, Weisheng (Frontiers in Microbiology, 2020)
Avian leukosis viruses (ALVs), a type of retrovirus responsible for various tumor diseases in chickens, are divided into 11 subgroups: ALV-A to ALV-K. After the envelope glycoproteins of ALV interact with the cellular receptor to initiate viral invasion, alterations in a few amino acids of the viral glycoproteins or cell receptors may trigger changes in their conformation and binding affinity. To identify the functional determinants of the ALV-K envelope protein that binds to Tva (a recently identified cellular receptor of ALV-K), using the strategy of continuous, segment-by-segment substitution of the gp85-encoded surface glycoprotein (SU) of ALV-K GDFX0602 with ALV-E ev-1 (Using Tvb as the receptor), a series of chimeric soluble gp85 proteins were expressed for co-immunoprecipitation analysis and a series of recombinant viruses with replication-competent avian retrovirus vectors containing Bryan polymerase (RCASBP) as their skeleton were created for transfecting to DF-1 cells and titer determination. The co-immunoprecipitation analysis, fluorescence-activated cell sorting and virus titer measurements revealed that the substitution of residues 194–198, 206–216 of hr1, residues 251-256 between hr1and hr2, residues 269-280 of hr2 were identified to reduce the binding of gp85 to Tva. The substitution of residues 194–221 in hr1 nullified the infectiveness of these viruses, similar to the effect of single amino acid mutations in K251E and L252I located between hr1 and hr2, continuous amino acid mutations in hr2 could not produce the same effect despite reducing their infectiveness. Finally, single amino acid mutations G196A and R198H nearly abolished the binding of gp85 to Tva and nullified the infectiveness of these viruses to DF-1. This study paves the way for exploring the molecular mechanisms of the binding of Tva to ALV-K SU.